(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effectiveness of toothpaste containing Selcopintide among residents aged 18–65 years in Thanh Xuan ward, Hanoi, in 2025. Methods: This was a clinical trial comparing three types of toothpaste: Selcopintide, Sodium Bicarbonate, and Fluoride. A total of 173 participants aged 18–65 years were followed up and included in the analysis. Results: After the intervention, all three toothpaste groups showed reductions in GI and PI scores over time, with statistically significant differences (p < 0.001). In the Selcopintide group, GI decreased from 1.93 ± 0.25 to 0.77 ± 0.42, corresponding to a 60.17% improvement at T6. In the Sodium Bicarbonate group, GI decreased from 2.05 ± 0.22 to 0.78 ± 0.42, corresponding to a 61.79% improvement. In the Fluoride group, GI decreased from 1.98 ± 0.14 to 1.06 ± 0.24, corresponding to a 46.60% improvement. PI also improved markedly, with reductions of 57.04% in the Selcopintide group, 58.59% in the Sodium Bicarbonate group, and 32.69% in the Fluoride group. Notably, the Selcopintide group showed an earlier improvement in GI during the T1–T3 period. Bleeding on probing also decreased substantially in all three groups, indicating a clear improvement in gingival health after the intervention. Conclusion: Toothpaste containing Selcopintide is effective in improving clinical gingivitis and may be widely used to improve oral health and prevent the progression to more severe periodontal complications.